Indo-Saracenic domes on the BMC building - Ghosh, Ayan (2023)
The Indo-Saracenic style developed by British architects used motifs inspired by Mughal architecture and those of the Deccan Sultanates, from monuments built by the Adil Shahis (Bijapur) and Qutub Shahis (Hyderabad) to make them look more ‘Indian‘. A prominent adaptation by Frederick W. Stevens was the use of the onion-shaped dome with a finial on top, which appears in buildings designed by him, including at the BMC.